Zinc finger proteins and the 3D organization of chromosomes - Feinauer, Christoph J.; Hofmann, Andreas; Liu, Lei; Máté, Gabriell; Heermann, Dieter W. (Advances in protein chemistry and structural biology, 2013)
Zinc finger domains are one of the most common structural motifs in eukaryotic cells, which employ the motif in some of their most important proteins (including TFIIIA, CTCF, and ZiF268). These DNA binding proteins contain up to 37 zinc finger domains connected by flexible linker regions. They have been shown to be important organizers of the 3D structure of chromosomes and as such are called the master weaver of the genome. Using NMR and numerical simulations, much progress has been made during the past few decades in understanding their various functions and their ways of binding to the DNA, but a large knowledge gap remains to be filled. One problem of the hitherto existing theoretical models of zinc finger protein DNA binding in this context is that they are aimed at describing specific binding. Furthermore, they exclusively focus on the microscopic details or approach the problem without considering such details at all. We present the Flexible Linker Model, which aims explicitly at describing nonspecific binding. It takes into account the most important effects of flexible linkers and allows a qualitative investigation of the effects of these linkers on the nonspecific binding affinity of zinc finger proteins to DNA. Our results indicate that the binding affinity is increased by the flexible linkers by several orders of magnitude. Moreover, they show that the binding map for proteins with more than one domain presents interesting structures, which have been neither observed nor described before, and can be interpreted to fit very well with existing theories of facilitated target location. The effect of the increased binding affinity is also in agreement with recent experiments that until now have lacked an explanation. We further explore the class of proteins with flexible linkers, which are unstructured until they bind. We have developed a methodology to characterize these flexible proteins. Employing the concept of barcodes, we propose a measure to compare such flexible proteins in terms of a similarity measure. This measure is validated by a comparison between a geometric similarity measure and the topological similarity measure that takes geometry as well as topology into account.
Gesehen am 18.08.2017